Assessment of Ocular Microbial Flora in Diabetic and Non- Diabetic Subjects Undergoing Cataract Surgery - Alok Vyas; Yeligeti Sai Praful Rag; Sagar Dhillon (Asian Journal of Medical Research, 2021)
Background: The aim is to assess ocular microbial flora in diabetic and non- diabetic subjects undergoing cataract surgery. Subjects and Methods: One hundred two adult patients were scheduled for cataract surgery. Fasting blood sugar (FBS), random blood glucose (RBG) and glycated hemoglobin level (HbA1c) was evaluated. Those with diabetes were kept in group I and healthy were kept in group II. Ocular flora was assessed in both groups. Results: Our results showed that Group I had 32 males and 30 females and group II had 24 males and 16 females. Group I comprised of 42% positive and 58% negative and group II had 20% positive and 80% negative microbial culture. Microorganism found to be staphylococcus coagulase-negative 24% in group I and 9% in group II, staphylococcus coagulase-positive 1% in group I and 4% in group II, Klebsiella 1% in group I and 2% in group II, staphylococcus epidermidis 6% in group I and 4% in group II, Enterobacter 0% in group I and 1% in group II and fungi in 10% in group I. Conclusion: Gram-negative bacteria, Klebsiella and Staphylococcus epidermidis were found to be higher in the conjunctival flora in diabetic patients as compared to healthy subjects.